Archidea - Forbo Flooring Systems (Amsterdam : Forbo Flooring Systems)
ArchIdea is a bi-annual magazine that features profiles well known and upcoming architects from all over the world. Connected to the architect presented ArchIdea covers a typical architectural feature that is linked to the architects' work. The magazine is published by Forbo Flooring Systems and also contains some of the latest projects in which our floor covering has been installed.
Zaha Hadid : 28 - Gert Wingardh : 29 - Hani Rashid, Asymptote : 30 - Toyo Ito : 31 - Helmut Jahn : 32 - Ben van Berkel : 34 - Jean Nouvel : 35 - Qingyun Ma : 36 - Fernando Romero : 37 - Ofis architects : 44 - Charles Renfro : 45 - Julien De Smedt : 46 - Kogan Aravena Iglesia : 47 - Emre Arolat : 48 - Mecanoo Hofmann Prego : 49 - Bjarke Ingels : 50 - Byoung Chgo - Zhang Ke - Sou Fujimoto : 51 - Lukasz Zagala : 52 - Andrés Jacque: 54 - Raul Pantaleo : 56 - Shih-Fu Peng : 58 -
Álvaro Siza Vieira : 6 - Gae Aulenti : 7 - Wes JOnes : 8 - Kerstin and Svante Berg : 9 - Paul Andreu : 11 - Alessandro Mendini : 12 - Richard Meier : 13 - Oscar Niemeyer : 14 - Jacques Herzog : 15 - Kai Wartiainen : 16 - Hundertwasser : 18 - Rafael Moneo : 19 - Henning Larsen : 20 - Jong Soung Kimm : 21 - Philip Cox : 22 - Bob van reeth : 23 - Imre Makovecz : 24 - Jo Noero : 25 - Mario Botta : 26 - Snohetta (Kjetil and Craig Dykers) : 27
Keywords: Architectuur